2002
DOI: 10.1210/jc.87.7.3433
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Localization of  -Catenin Correlates with Overexpression of Its Target Gene in Human Papillary Thyroid Cancer

Abstract: Alterations of the Wnt/beta-catenin signaling pathway are known to occur in mutations of the component genes such as APC, Axin, and beta-catenin, and play a pathogenetic role in tumorigenesis. Activated Wnt signaling stabilizes beta-catenin, which associates with T cell factor, resulting in transactivation of the downstream target genes including c-myc and cyclin D1. To investigate the involvement of Wnt/beta-catenin signaling pathway in thyroid tumorigenesis, we analyzed its activation and localization in 5 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 0 publications
4
39
0
1
Order By: Relevance
“…31,32,39,[59][60][61][62][63][64] An alteration in the gene encoding cyclin D1 has not been reported in thyroid neoplasia, but a link between aberrant b-catenin expression and upregulation of cyclin D1 has been shown in a variety of neoplasms. [65][66][67] In this study, the nuclear expression of cyclin D1 was markedly increased in the vast majority of indolent and aggressive neoplasms. This finding contrasts with conventional papillary thyroid carcinomas in which cyclin D1 is only expressed in a low percentage of neoplastic cells.…”
Section: Discussionmentioning
confidence: 49%
“…31,32,39,[59][60][61][62][63][64] An alteration in the gene encoding cyclin D1 has not been reported in thyroid neoplasia, but a link between aberrant b-catenin expression and upregulation of cyclin D1 has been shown in a variety of neoplasms. [65][66][67] In this study, the nuclear expression of cyclin D1 was markedly increased in the vast majority of indolent and aggressive neoplasms. This finding contrasts with conventional papillary thyroid carcinomas in which cyclin D1 is only expressed in a low percentage of neoplastic cells.…”
Section: Discussionmentioning
confidence: 49%
“…Our data are in partial agreement with the aberrant expression and localization of b-catenin that has been reported in a variety of human cancers including colon, 36 liver, 37 stomach, 38 pancreas, 39 bone, 40 and thyroid. 41 Reports that have studied the expression of b-catenin in human lung cancer remain controversial. Some authors, in agreement with the present observations, reported restricted cytoplasmic localization and never found b-catenin nuclear translocation, 34,[42][43][44][45] whereas some other studies show cytoplasmic and nuclear localization of b-catenin.…”
Section: Discussionmentioning
confidence: 99%
“…Such mutations disrupt phosphorylation sites of -catenin and lead to protein stabilization. Mutations and abnormal nuclear localization of -catenin have been observed, along with overexpression of its target genes c-Myc and cyclin D1, in thyroid malignancies (Ishigaki et al, 2002). Although increased levels of cytoplasmic -catenin are observed in most thyroid cancer cells, mutations of -catenin that lead to nuclear localization of the protein are limited to PDTC and ATC suggesting a role in tumor progression (Garcia-Rostan et al, 2001).…”
Section: Genetic Alterations In Anaplastic Thyroid Carcinomasmentioning
confidence: 99%